DYNAMIC PRICING ALGORITHM IN PARKING SYSTEMS - Hari Sundar, Hari Saresh (IRC, 2020)
This project discusses on using a different approach to an already existing dynamic algorithm for the parking rate in a parking lot to conclude if the new approach is effective in determining the optimal parking rate based on the current demand of a parking lot. As the number of on-road vehicles are expected to increase in the coming years, parkers are encouraged or discouraged into using a parking lot based on the current demand of the parking lot. This algorithm will be used to change the parking rate in any parking lots that maybe overutilised or underutilised. Based on the study done using dynamic pricing algorithm as well the results were encouraging and showed a reduction in congestion and underuse of the parking lots (Zoeter, Dance, Clinchant, & Andreoli, 2014). This algorithm will be built differently and the analysis will be done on whether the new algorithm will be an improvement to the previous algorithm done in another paper. This algorithm if successful, will be proposed to be incorporated into a parking system and hence it requires it to be straightforward and simple as well so that the parkers will understand how the system operates.